The Risk in Discretion: Substantive NEPA’s Significance - Colburn, Jamison E. (Columbia Journal of Environmental Law, 2019)
Every student of the National Environmental Policy Act (“NEPA”) knows that it is a “procedural” statute. Its practical difference as law is to force agencies to take a “hard look” at their proposed actions before taking them. NEPA’s broadest goal—that the government “foster and promote the general welfare, to create and maintain conditions under which man and nature can exist in productive harmony, and fulfill the social, economic, and other requirements of present and future generations”—is not, by contrast, law to be enforced. In short, NEPA’s ultimate goal of making American society more sustainable has been marginalized even as its chief procedural tool—the Environmental Impact Statement (“EIS”)—has become ubiquitous. NEPA section 102(2)(C) clearly mandates in a modally unmistakable way that “all agencies of the Federal government,” when taking any “major Federal action[] significantly affecting the quality of the human environment,” prepare an EIS, specifying some of the contents thereof. Nothing in the statute even comes close to doing so for its more substantive objectives. For all the judicial pronouncements that NEPA is an “essentially procedural” statute, the question remains whether any such pronouncements bind the executive branch, preventing it from putting NEPA’s more substantive aspects into effect. The Supreme Court has held that “[b]efore a judicial construction of a statute . . . may trump an agency’s, the court must hold that the statute unambiguously requires the court’s construction.” Such holdings need not be expressed in these exact terms, but the Court’s formula clearly empowers the executive. Indeed, a judicial construction only binds as to the “precise question at issue.” Are there any such precedents in NEPA’s past? If so, how should they inform the President, whose duty and power it is to “take care” that the “Laws be faithfully executed”?